Lakon Karna Tandhing: Konsep Pergantian Musim dalam Pemujaan Syiwa - Aris Wahyudi (Institut Seni Indonesia Yogyakarta, 2019)
Arjuna, Indra’s son stands at his war car. General uniform was used making heroic, his left hand hold a bow, and right hand to balance arrow; in the other side Kurawa’s army, Prabu Karna, the Surya’s son, the commander to play his bow too. When bang of war drum to fill the sky, the both army toward central of Kuruksetra field. The millionarrows flaying in the sky like cloudy that closed the sun, and after their hundreds army to yell out dating, afterward the Kuruksetra field flood blood. Suddenly Karna’s arrow kicks Arjuna’s head. At once surprised who show it. Deities yell congratulation praying. Some minutes the war stop. Arjuna’s crown destroyed. Narada descends from the sky give crown to Arjuna that it is exactly with Karna’s have. The both hero collide again. Now, Arjuna likes Karna. Arjuna.s angry make increasingly. He get Pasopati arrow. Arjuna lift his bow. Another one who is look when Arjuna frees his arrow, suddenly Karna’s head cut off. Kurawa’s Hero, Surya’s son was dead. This story, in the wayang world it was called Lakon Karno Tandhing. There were can to get some problems. When Arjuna’s crown destroyed, Narada prepare a crown to Arjuna. I assume that deity knew that would happen. The question is “Why the crown was prepared similarly Karna have, so it is called Karna Tandhing? I am sure that the composer had a meaning ofit. Mythology-ritual analysis shows that this happen is continuity of deity level. All of the hero experiences always involve deity activities. Javanese philosopher composed this story to explain cosmic system that uses symbol systems Lakon Karna Tandhing.Arjuna, putra Indra berdiri megah di atas kereta perangnya. Pakaian kebesaran seorang senapati semakin menambah keperkasaannya. Kedua tangannya mengayun gendewa lengkap dengan busurnya. Di pihak lain, Prabu Karna, putra Surya melakukan hal yang sama saat memimpin pasukan Kurawa. Begitu genderang perang bertalu-talu memenuhi angkasa, kedua pihak berhambur ke medan Kuruksetra, saling menyerbu. Ribuan pasukan saling bertempur dan tidak sedikit yang gugur. Tiba-tiba anak panah Karna menghantam kepala Arjuna hingga mahkotanya hancur. Semua yang menyaksikan sangat terkejut, termasuk pula para dewa dewi di angkasa. Narada segera turun ke dunia, memberikan mahkota yang mirip dengan yang dikenakan Karna yang membuat Arjuna mirip dengan Karna. Kedua perwira tersebut kembali bertempur, seakan-akan Karna melawan Karna. Arjuna melepaskan panah pasopati dan tepat memenggal leher Karna. Karna gugur dengan kepala terlempar dan tubuhnya bersandar di kereta perangnya. Kisah ini dalam tradisi pedalangan disebut lakon Karna Tandhing. Dari persoalan tersebut, pertanyaannya adalah: mengapa mahkota yang diberikan Narada tersebut mirip dengan milik Karna? Melalui analisis mitologi-ritual diperoleh pemahaman bahwa peristiwa tersebut merupakan kontinuitas dari peristiwa di tataran mite. Semua peristiwa yang dialami para tokoh epic selalu melibatkan campur tangan tokoh mite. Lakon Karna Tandhing merupakan pengejawantahan peristiwa kosmis yang menjelaskan perpindahan musim kemarau (Karna sebagai putra Surya) berganti dengan musin penghujan (Arjuna sebagai putra Indra). Kesemuanya diatur oleh Syiwa sebagai mahakala yang disimbolkan melaluiArjuna bermahkotakan “Karna”.